DISFEMISME DALAM TUTURAN MASYARAKAT KECAMATAN TAPUNG HULU - Muhammad Rizki; Dudung Burhanudin; Charlina ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study was to discuss disfemism in publicstatements Tapung Hulu of the sub-district. This study aims to describe the form andfunction of Tapung District of Hulu of the speech community. In this study, the datasource in this study were persons residing in the Tapung Hulu district. The search fordata by the author is the sentence that contains disfemism in public statements TapungHulu of the sub-district. Data collection techniques in speech research disfemismTapung Hulu community using techniques of subdistrict interview and recordingtechnique by finding phrases containing disfemism in the district community of theTapung Hulu speech. This method is operationalized by collecting data relevant to theanalysis analysis penulisan.Teknik used in the analysis of data on sentences containingdisfemism analysis techniques namely descriptive. Descriptive analysis techniques areused to describe the form and function of Hulu's Tapung district of the speechcommunity. The search data comprises data 100 which consists of 55 forms of a word,expression form data 24 and 21, in the form of expression data.Keywords: Disfemism